Vacuum induced Berry phase: theory and experimental proposal - Bose, S; Carollo, A; Fuentes-Guridi, I; Franca Santos, M; Vedral, V (2003)
We investigate quantum effects in geometric phases arising when a two-level system is interacting with a quantized electromagnetic field. When the system is adiabatically driven along a closed loop in the parameter space, signatures of the field quantization are observable in the geometric phase. We propose a feasible experiment to measure these effects in cavity QED and also analyse the semi-classical limit, recovering the usual Berry phase results.